Long-lasting multi-surface disinfectant: Evaluation of efficiency and durability - Débora Castro; Isabel Ferreri; Isabel Carvalho; Mariana Henriques (Results in Engineering, 2022)
The present work aimed to study the efficacy and durability of a long-term multi-surface disinfectant. The disinfectant formulation understudy had hydrogen peroxide and ethanol as active substances, among other substances. The antimicrobial activity of the formulation components and their stability on porous, non-porous, and everyday surfaces was evaluated. The stability test result show that the disinfectant still has antimicrobial activity after 2 years of storage, even with the loss of 80% of one of the active substances. The results show that the disinfectant has an impressive antimicrobial activity for porous surfaces and good performance for non-porous surfaces. The analysis of antimicrobial activity on everyday surfaces shows total fungal inhibition and a notable decrease in bacteria colonization after 7 days of disinfectant application.